The analysis of unreliable M[X]/G/1 queuing system with loss, vacation and two delays of verification. Issue 5 (28th May 2019) - Saggou, Hafida; Sadeg, Ines; Ourbih-Tari, Megdouda; Bourennane, El-Bay
ABSTRACT: This paper considers an M [ X ] / G /1 queue with breakdowns, repair, Bernoulli vacation, two delays and geometric loss. In this paper, a special attention is given to the limiting distribution of system states. We obtain simplified expressions for the Probability Generating Functions (PGFs) of the joint distribution of server state and system size. Some performance measures were derived from the analysis of the steady state probabilities. PGF of a departure point system size distribution is developed. Particular cases of the studied system were investigated. The effect of system parameters on the main performance measures are illustrated and discussed.